Effects of Export Externalities on Peru's GDP Growth, 2008-2022 - Rojas Lara, Pablo Enrique (2024)
This study aims to examine the relationship between export externalities and economic growth at the industrial level in Peru between 2008 and 2022, in an effort to test the hypothesis that there are heterogeneous effects of trade on domestic industries. Based on endogenous growth theory and Feder's work, an econometric panel data model is formulated to measure the relationship between the described variables and the industrial GDP growth rate. The results suggest the existence of a positive and significant effect of export externalities on GDP, regardless of the panel model used.